TRADISI PINANGAN ADAT PERNIKAAN SUKU BAURAH ALOR KECIL DI KABUPATEN ALOR - Lisa Victoria Malimou; Jesenia Loryance Alelang, Lambertus Lupuikoni, Lea Adangjaha, Isak Fantang , Jero Sion Exssal Blegur (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to examine the tradition of the Pinangan Tradition of the Baurah Alor Kecil Tribe in Alor Regency, the research data analysis uses qualitative descriptive analysis, the data used in the research is qualitative data. Data collection techniques through field observations and interviews, interviews with Mr Sulaiman Oramahi. The proposal tradition, known as Akat Nika, is part of the marriage customs practised by the Baurah Tribe. This tradition has a deep meaning in honouring the bride's parents and strengthening the relationship between the families of the two brides. Through this research, it is hoped that the values contained in the proposal tradition and the way the community maintains this tradition in traditional marriages can be known. The results show that the proposal tradition is still upheld and passed down from generation to generation as part of the cultural identity of the Alor Kecil community.